First report and genetic characterization of Seneca Valley virus (SVV) in Chile. Issue 6 (11th November 2022) - Bennett, Benjamín; Urzúa‐Encina, Constanza; Pardo‐Roa, Catalina; Ariyama, Naomi; Lecocq, Claudio; Rivera, Carlos; Badía, Catalina; Suárez, Paulina; Agredo, Michel; Aguayo, Carolina; Ávila, Claudia; Araya, Hugo; et al.
Abstract: Seneca Valley virus (SVV) is a non‐enveloped RNA virus and the only member of the Senecavirus A (SVA) species, in the Senecavirus genus, Picornaviridae family. SVV infection causes vesicular lesions in the oral cavity, snout and hooves of pigs. This infection is clinically indistinguishable from trade‐restrictions‐related diseases such as foot‐and‐mouth disease. Other clinical manifestations include diarrhoea, anorexia, lethargy, neurological signs and mortality in piglets during their first week of age. Before this study, Chile was considered free of vesicular diseases of swine, including SVV. In April 2022, a suspected case of vesicular disease in a swine farm was reported in Chile. The SVV was confirmed and other vesicular diseases were ruled out. An epidemiological investigation and phylogenetic analyses were performed to identify the origin and extent of the outbreak. Three hundred ninety‐five samples from 44 swine farms were collected, including faeces (208), oral fluid (28), processing fluid (14), fresh semen (61), environmental samples (80) and tissue from lesions (4) for real‐time RT‐PCR detection. Until June 2022, the SVV has been detected in 16 out of 44 farms, all epidemiologically related to the index farm. The closest phylogenetic relationship of the Chilean SVV strain is with viruses collected from swine in California in 2017. The direct cause of the SVV introduction has not yet been identified; however, the phylogenetic analyses suggest the USA as the most likely source. Since the virus remains active in the environment, transmission by fomites such as contaminated feed cannot be discarded. Further studies are needed to determine the risk of the introduction of novel SVV and other transboundary swine pathogens to Chile.